1999
DOI: 10.1007/s001150050450
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeale Aussaat einer chronisch lymphatischen Leukämie

Abstract: The diagnosis of leptomeningeal dissemination of chronic lymphatic leukemia (CLL) by conventional cytology is unreliable because cytomorphologic criteria of malignancy are often lacking. Immunophenotyping of leukocyte differentiation antigens may also be of limited diagnostic value due to the small number of cells in cerebrospinal fluid (CSF) samples. Molecular methods may support the specific diagnosis of leptomeningeal infiltration of CLL. We present an 54 old patient who was diagnosed with CLL five years ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our results demonstrate that PCR-based automated fluorescent fragment analysis of IgH CDR3 sequences is of clinical importance if diagnostic problems arise in the distinction of acute demyelinating disorders and pC-NSL, which are tumours of B cell origin in the vast majority of cases [9].We have recently shown this technique to be an excellent diagnostic tool in the assessment of lymphomatous meningitis, where low CSF cell numbers frequently limit the utility of immunophenotyping analysis [17,18]. Unlike reactively transformed lymphocytes originating from clonally diverse B cells, derivatives of a malignant B cell clone carry identically rearranged CDR3 loci, and their molecular detection using the PCR assay described reliably generates monoclonal fragments of distinct fluorescence intensity and size [13,15,17,18].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results demonstrate that PCR-based automated fluorescent fragment analysis of IgH CDR3 sequences is of clinical importance if diagnostic problems arise in the distinction of acute demyelinating disorders and pC-NSL, which are tumours of B cell origin in the vast majority of cases [9].We have recently shown this technique to be an excellent diagnostic tool in the assessment of lymphomatous meningitis, where low CSF cell numbers frequently limit the utility of immunophenotyping analysis [17,18]. Unlike reactively transformed lymphocytes originating from clonally diverse B cells, derivatives of a malignant B cell clone carry identically rearranged CDR3 loci, and their molecular detection using the PCR assay described reliably generates monoclonal fragments of distinct fluorescence intensity and size [13,15,17,18].…”
Section: Discussionmentioning
confidence: 79%
“…Unlike reactively transformed lymphocytes originating from clonally diverse B cells, derivatives of a malignant B cell clone carry identically rearranged CDR3 loci, and their molecular detection using the PCR assay described reliably generates monoclonal fragments of distinct fluorescence intensity and size [13,15,17,18]. In none of the three cases described here could lymphoma be excluded with certainty since multifocal white matter lesions appeared of uniform age, as revealed by marked contrast enhancement on cranial MRI, and CSF cytology suggested possible neoplastic transformation of CSF lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vogt-Schaden and colleagues (1999) confirmed leptomeningeal dissemination in a patient with CLL using a clone-specific CDR3 region in IgH encoding locus. It has already been reported in a study about lymphomas and reactive lymphoid proliferations that the use of both FCI and PCR techniques in different sample specimens [ 77 ]. The authors observed a superior sensitivity of FCM when compared with PCR (77% vs 64%).…”
Section: Discussionmentioning
confidence: 99%